PENDIDIKAN AKHLAK ANAK USIA DINI BERBASIS FITRAH DI TAUD SAQU DAR EL IMAN KOTA PADANG - Deti Yulia Martiana; Syafrul Nalus; Muhammad Zalnur (As-Sulthan Journal of Education, 2026)
This study aims to analyze the nature-based moral education of early childhood at TAUD SAQU Dar El Iman, Padang City. The study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, then analyzed interactively and continuously. The results indicate that nature-based moral education is implemented through teacher role models, the instillation of religious values, and the creation of a conducive Islamic educational environment. Moral education is not directed at shaping children's behavior externally, but rather at developing the moral and spiritual potential inherent in children from birth. The novelty of this study lies in the operationalization of the concept of nature as an applicable pedagogical paradigm in early childhood education, thus providing conceptual and practical contributions to the development of nature-based moral education in Islamic PAUD institutions.